Influence of Gender and Race/Ethnicity on Perceived Barriers to Help-Seeking for Alcohol or Drug Problems - Verissimo, Angie Denisse Otiniano (J Subst Abuse Treat, 2017)
This study examines reasons why people do not seek help for alcohol or drug problems by gender and race/ethnicity using data from the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC), a nationally representative survey. Multivariate models were fit for 3 barriers to seeking help (structural, attitudinal, and readiness for change) for either alcohol or drug problems, controlling for socio-demographic characteristics and problem severity. Predicted probabilities were generated to evaluate gender differences by racial/ethnic subgroups. Over three quarters of the samples endorsed attitudinal barriers related to either alcohol or drug use. Generally, women were less likely to endorse attitudinal barriers for alcohol problems. African Americans and Latina/os were less likely than Whites to endorse attitudinal barriers for alcohol problems, Latina/os were less likely than Whites to endorse readiness for change barriers for alcohol and drug problems, however, African Americans were more likely to endorse structural barriers for alcohol problems. Comparisons within racial/ethnic subgroups by gender revealed more complex findings, although across all racial/ethnic groups women endorsed attitudinal barriers for alcohol problems more than men. Study findings suggest the need to tailor interventions to increase access to help for alcohol and drug problems that take into consideration both attitudinal and structural barriers and how these vary across groups.